CD147 overexpression allows an accurate discrimination of bladder cancer patients’ prognosis - Afonso, J. (2011)
Background: Urothelial bladder carcinoma (UBC) is a chemo-sensitive tumour, but the response to treatment is heterogeneous. CD147 has been associated with chemotherapy resistance. We aimed to define tumours with an aggressive phenotype by the combined analysis of clinicopathological and biological parameters. Methods: 77 patients with T1G3 or muscle-invasive UBC treated by radical cystectomy were studied. Immunohistochemistry was performed to detect CD147, heparanase, CD31 (blood vessels identification) and D2-40 (lymphatic vessels identification) expressions. The immunohistochemical reactions were correlated with the clinicopathological and the outcome parameters. 5-year disease free survival (DFS) and overall survival (OS) rates were estimated using the Kaplan-Meier method. Multivariate analysis was performed by Cox proportional hazards analysis. Results: The 5-year DFS and OS rates were significantly influenced by the classical clinicopathological parameters, and by the occurrence of lymphovascular invasion. CD147 and heparanase immunoexpression did not affect patients’ outcome. However, patients with pT3/pT4 tumours had a median OS time of 14.7 months (95% CI 7.1-22.3, p=0.003), which was reduced to 9.2 months (95% CI 1.5-17.0, p=0.008) if the tumours were CD147 positive. We developed a model of tumour aggressiveness using parameters as stage, grade, lymphovascular invasion and CD147 immunoexpression, which separated a low aggressiveness from a high aggressiveness group, remaining as an independent prognostic factor of DFS (HR 3.746; 95% CI 1.244-11.285; p=0.019) and OS (HR 3.247; 95% CI 1.015-10.388, p=0.047). Conclusion: CD147 overexpression, included in a model of UBC aggressiveness, may help surgeons to identify patients who could benefit from a personalized therapeutic regimen. Additional validation is needed.